Etiology of Renal Tubulopathy in Iranian Children-A Nationwide Survey - Hooman, Nakysa; Derakhshan, Ali; JavadiLarijani, Faezeh (Journal of Pediatric Nephrology, 2018)
Introduction: Inherited and acquired renal tubular disorders including cystic Kidney disease, cystinosis, Bartter’s syndrome, Liddle syndrome, Gordon syndrome, nephrogenic diabetes insipidus, and drug-induced tubular injury are the frequent causes of end stage renal disease (ESRD) in children manifesting with chronic kidney disease (CKD). This is a report of the etiology and incidence of tubulopathies in a cohort of Iranian children across the country. Materials and Methods: This descriptive observational study was conducted from March 2013 to October 2013. A list of tubulopathy disorders was emailed to 70 members of the Iranian Society of Pediatric Nephrology in different provinces of Iran practicing in both university affiliated and non-affiliated hospitals. They were requested to report the number of patients with specific International Classification of Disease (ICD-10) codes admitted to their hospitals between 2006 and 2013. Data are presented as numbers and percentages. Results: Of 31 participating centers, 23 completed and returned the spreadsheets. Of the 2940 reported cases,the three most frequent tubulopathies were renal tubular acidosis (RTA) (33%), calcium disorders (27%), and cystic diseases (17%). Considering Tehran and Shiraz as referral centers, RTA and cystinosis were mostly reported from Kermanand Urmia, respectively. Furthermore, idiopathic hypercalciuria, cystinuria, and hyperoxaluria were the most common causes of hereditary kidney stone in 281 children reported from Bandarabas, Tabriz, and Shiraz, respectively Conclusions: Our findings regarding the high incidence and different etiologies of inherited tubulopathies may provide a basis for designing targeted therapeutic interventions in the future and strategies for gene therapy of these complex disorders. Keywords: Kidney Tubules; Disease; Acidosis; Renal Tubule; Kidney disease; Cyst; Diabetes Insipidus; Urolithiasis; Bartter syndrome.